Operation Pedro Pan and the exodus of Cuba's children - Shnookal, Deborah (University of Florida Press, 2020)
"This examination of one of the most controversial episodes in U.S.-Cuba relations sheds new light on Operation Pedro Pan, the program that airlifted 14,000 unaccompanied children to the United States in the wake of the Cuban Revolution"--